THAP11 Functions as a Tumor Suppressor in Gastric Cancer through Regulating c-Myc Signaling Pathways. (28th August 2020) - Zhang, Jing; Zhang, Huahua; Shi, Haiyan; Wang, Fenghui; Du, Juan; Wang, Yu; Wei, Yameng; Xue, Wanjuan; Li, Dan; Feng, Yun; Yan, Jing; Gao, Yi; et al.
Abstract : We aim to investigate the role of THAP11 (thanatos-associated protein11) in gastric cancer and its regulation mechanisms. THAP11 expression was analyzed in 51 pairs of GC tissues and the corresponding paracancerous tissues by qRT-PCR and Western blot. After THAP11 was overexpressed or knocked-down, cell proliferation, cell cycle, and apoptosis were detected in MKN-45 cells. We found that THAP11 was significantly downregulated in GC tissues and GC cell lines. Functionally, THAP11 overexpression markedly inhibited cell growth, induced G1/G0 cell-cycle arrest, and promoted cell apoptosis of MKN-45 cells, while silencing of THAP11 led to increased cell growth, increased DNA synthesis, and inhibited apoptosis. In addition, THAP11 negatively regulated the expression of c-Myc, decreased cyclinD1 protein, and increased p27 and p21 protein levels. We also found cell growth suppression induced by THAP11 was rescued by c-Myc overexpression, further confirming that THAP11 suppresses gastric cancer cell growth via the c-Myc pathway. THAP11 acts as a cell growth suppressor and exerts its role possibly through negatively regulating c-Myc pathway in gastric cancer.